The Influence of Work-Life Balance and Physical Work Environment on Employee Performance with Work Stress as an Intervening Variable - Naisoko, Wirneria Susana; Amleni, Rosarianto Mariano (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2026)
This study aims to examine the influence of Work-Life Balance and the Physical Work Environment on Employee Performance, with Work Stress as an Intervening Variable, in the Pamong Praja Police Unit of North Central Timor Regency. Using a quantitative approach, a simple random sampling technique was employed to gather data from 83 employees of the North Central Timor Regency Pamong Praja Police Unit. The data analysis techniques used are inner model analysis, outer model analysis, and model fit test. The analysis revealed that both Work-Life Balance and Physical Work Environment positively affect Employee Performance, specifically mediated by levels of Work Stress. The T-test results demonstrated significant statistical evidence (T statistic > T table) for these relationships. It was recommended that organizations take steps to improve the work-life balance and physical work environment to improve the level of employee performance.